Siti Walidah’s Gender Vision and Islamic Feminist Pedagogy: Reconstructing Islamic Educational Epistemology in Mu’allimat Yogyakarta - Renci Renci; An-Najmi Fikri Ramadhan; Ikrima Maulida (Journal of Islamic Education and Intellectual Discourse (JIED), 2026)
Women's education in Indonesia has progressed significantly, yet gender inequality within Islamic educational spaces remains a critical issue. This study aims to re-examine the continuity of the gender justice vision initiated by Siti Walidah in founding Madrasah Mu’allimaat Muhammadiyah Yogyakarta within contemporary educational practices. This study employed a qualitative case study design with a multi-source data triangulation strategy, including the analysis of official institutional documents such as the Curriculum and the 2024 Student Rules and Regulations, tracking institutional digital traces, and syntheses of previous field studies. The data were analyzed through the lens of bell hooks' feminist framework of engaged pedagogy to dissect the relationships between teachers, students, and social structures. The findings demonstrate that the implementation of feminist pedagogy within Madrasah Mu’allimaat has successfully transformed these relationships through three main interaction dimensions. First, regarding the teacher-student relationship, the institution has dismantled the dominance of banking education by positioning teachers as dialogic mentoring partners who restore students' voices as empowered subjects. Second, the application of experience-based dialogic education successfully transforms the learning process into an act of liberation that sharpens students' critical consciousness. Third, in terms of its connection to social structures, the institution utilizes a single-sex environment and protective rules and regulations as an inclusive safe space to train students' leadership agency without external gender intervention. This study concludes that Siti Walidah's tauhid-based vision of emancipation has been successfully codified into a modern institutional legal system that functionally prepares Muslim women to transform and deconstruct patriarchal social structures in wider society.